Survival-associated factors of first-line EGFR-tyrosine kinase inhibitor responders and non-responders in lung adenocarcinoma patients with common EGFR mutations - Hung, Ming-Szu (Mol Clin Oncol, 2018)
The aim of the present retrospective cohort study was to elucidate the clinical presentation of epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) responders and non-responders in lung adenocarcinoma patients with common EGFR mutations. The cohort included 131 lung adenocarcinoma patients with common exon 19 or exon 21 EGFR mutations, who were receiving first-line EGFR-TKI therapy. The patient characteristics, treatment regimen and outcomes were recorded and analyzed. Of the 131 patients, 104 (79.3%) responded to treatment, while 27 (20.7%) did not. A significantly longer median progression-free survival (PFS) [14.3, 95% confidence interval (CI): 12.2–18.4 vs. 5.7, 95% CI: 2.7–9.9 months; P<0.001] and overall survival (OS) (42.2, 95% CI: 28.1–58.1 vs. 11.5, 95% CI: 8.3–19.7 months; P<0.001) were observed in responders compared with non-responders. In responders, bone [hazard ratio (HR)=1.87, 95% CI: 1.11–3.20, P=0.021] and pleural (HR=2.40, 95% CI: 1.37–4.22, P=0.002) metastasis were independent factors of PFS. Exon 19 mutations (HR=0.38, 95% CI: 0.19–0.76, P=0.006), Eastern Cooperative Oncology Group performance status score ≥2 (HR=3.53, 95% CI: 1.42–8.75, P=0.007) and bone metastasis (HR=2.01, 95% CI: 1.05–3.85, P=0.034), were independent factors of OS. In non-responders, smoking (HR=3.97, 95% CI: 1.13–13.91, P=0.031) was an independent factor of PFS. Different survival-associated factors were observed between EGFR-TKI responders and non-responders. The development of new treatment strategies should be advocated in EGFR-TKI non-responders.